Diffusion of Linguistic Functions in the Synonymy of "Demikian" and "Begitu" in 160-Year Literary Work - Nurina Azyyati; Dwi Linda Kusuma; Nurrahma Restia Fatkhiyati (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study explores the language change that occurred in two Indonesian demonstrative words, “demikian” and “begitu”, which are synonyms. As synonyms, both have similar linguistic functions. This study examines the possibility of language change influenced by synonymy through the diffusion of their linguistic functions. The literature works used in this study are Hikayat Abdullah (1842), Azab dan Sengsara (1920), and Cantik Itu Luka (2002), covering a period of 160 years. The words ‘demikian’ and ‘begitu’ were collected by using AntConc and were classified based on the level of change that occurred. The diffusion of their linguistic functions is then supported by quantitative data in the form of frequency. The analysis found that the changes in the word ‘demikian’ are influenced by its synonym: the word ‘begitu’. Consequently, in the 21st century, the word ‘demikian’ has become similar to its synonym. This study may be useful to portray how language change occurs in synonyms as a specific linguistic category. It can also point out the direction of language change which can be useful for further discussion on language policy.